The Role of Profitability as a Mediator in the Effect of Liquidity and Leverage on Financial Distress Prediction Using the Zmijewski Method - Kharisma Sofi Febiana; Nurdiniah, Dade (Universitas Pamulang, 2025)
The increasing number of companies at risk of delisting from the Indonesia Stock Exchange emphasizes the need for early detection of financial distress. This study aims to examine the effect of liquidity and leverage on financial distress, with profitability as a mediating variable. The research population includes all Consumer Cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample consists of companies listed on the Watchlist board and reporting financial statements in Rupiah. Liquidity is measured by Current Ratio (CR), leverage by Debt to Asset Ratio (DAR), profitability by Return on Assets (ROA), and financial distress by the Zmijewski method. The results show that liquidity does not affect profitability, while leverage has a significant negative effect. Liquidity and leverage both significantly affect financial distress. Profitability partially mediates the effect of leverage on financial distress, but cannot mediate the effect of liquidity on financial distress.